Why so low? An unusual case of myositis in a child - Meagan E. Chriswell; Robert C. Fuhlbrigge; Mark A. Lovell; Matthew Monson; Jessica L. Bloom (BMC, 2023)
Abstract Background Sarcoidosis is characterized by non-caseating epithelioid granulomas in various tissues throughout the body, most commonly the lung. Non-caseating granulomas may be seen in skeletal muscle, though typically asymptomatic and under-recognized. While rare in children, there is a need to better characterize the disease and its management. Here we present a 12-year-old female with bilateral calf pain who was ultimately found to have sarcoid myositis. Case Presentation A 12-year-old female presented to rheumatology with significantly elevated inflammatory markers and isolated lower leg pain. MRI of the distal lower extremities demonstrated extensive bilateral myositis with active inflammation, atrophy, and to a lesser extent fasciitis. This distribution of myositis in a child garnered a broad differential requiring a systematic evaluation. Ultimately, muscle biopsy revealed non-caseating granulomatous myositis with perivascular inflammation, extensive muscle fibrosis, and fatty replacement of the muscle with a CD4+ T cell predominant, lymphohistiocytic infiltrate consistent with sarcoidosis. Review of histopathology from age 6 of an extraconal mass resected from her right superior rectus muscle further confirmed the diagnosis. She had no other clinical symptoms or findings of sarcoidosis. The patient improved significantly with methotrexate and prednisone, though flared again after self-discontinuation of medications and was subsequently lost to follow-up. Conclusion This is the second reported case of granulomatous myositis associated with sarcoidosis in a pediatric patient, and the first to present with a chief complaint of leg pain. Increased knowledge of pediatric sarcoid myositis within the medical community will enhance recognition of the disease, improve the evaluation of lower leg myositis, and advance outcomes for this vulnerable population.